2021
DOI: 10.3390/antiox10030413
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophylls Modulate Palmitoylation of Mammalian β-Carotene Oxygenase 2

Abstract: An extensive body of work has documented the antioxidant role of xanthophylls (lutein and zeaxanthin) in human health and specifically how they provide photoprotection in human vision. More recently, evidence is emerging for the transcriptional regulation of antioxidant response by lutein/lutein cleavage products, similar to the role of β-carotene cleavage products in the modulation of retinoic acid receptors. Supplementation with xanthophylls also provides additional benefits for the prevention of age-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…However, more work is needed to clarify whether these xanthophylls act by modulating redox-signaling pathways or by binding directly to ligand-activated receptor proteins that function in gene regulation. The possibility has been suggested that the cleavage products of zeaxanthin and lutein [105] may bind to such ligand-activated receptors [106,107]. The oxidation products of carotenoids may also act as signaling molecules in plants [16].…”
Section: Carotenoids and Gene Expression In Plants And Humansmentioning
confidence: 99%
“…However, more work is needed to clarify whether these xanthophylls act by modulating redox-signaling pathways or by binding directly to ligand-activated receptor proteins that function in gene regulation. The possibility has been suggested that the cleavage products of zeaxanthin and lutein [105] may bind to such ligand-activated receptors [106,107]. The oxidation products of carotenoids may also act as signaling molecules in plants [16].…”
Section: Carotenoids and Gene Expression In Plants And Humansmentioning
confidence: 99%
“…In addition, very recently, it was also reported that mouse carotene-9′,10′-oxygenase (BCDO2 also called BCO2, details of the function of this carotenoid-substrate enzyme are described in Section 2.2.3 and Section 2.2.6 ) is a functionally palmitoylated enzyme that, upon binding to xanthophylls in the mitochondria, can be translocated into the nucleus via depalmitoylation. Once in the nucleus, it may bind to AREs, possibly in association with other transcription factors such as Nrf2, and then regulate downstream gene expression [ 103 ]. It has been reported that mice with whole-body knockout of BCDO2 function developed metabolic dysfunction derived from the peripheral and hypothalamus, even when fed a diet thought to be free of carotenoids.…”
Section: Mechanism By Which Astaxanthin Enhances Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…In relation to AX, the effect of BCDO2-generated AX metabolites should be considered in the future, because it has only been studied in toxicological aspects, such as CYP induction in rats [ 125 ]. Perhaps independently of these features, BCDO2 itself probably functions as an anti-inflammatory factor through the modulation of several signaling pathways and gene expression [ 103 , 104 , 105 , 106 , 236 , 237 ].…”
Section: Mechanism By Which Astaxanthin Enhances Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…Xanthophylls have multi-focal activity. Among others, their antibacterial [11], antibiofilm [12], antioxidant [13,14], anti-inflammatory [13,15] and anticancer [16] activities have been described. The latest publications indicate that xanthophylls may also have a protective effect in the course of COVID-19 [17,18].…”
Section: Introductionmentioning
confidence: 99%